ISLAMIC FINANCIAL LITERACY, DIGITAL PAYMENT, AND GENERATION Z’S INTENTION TO USE SHARIA FINTECH - Farhan Zikry; Fazil; Siti Fatimah; Zulaiva Ulya (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the influence of Islamic financial literacy and digital payment on Generation Z’s intention to use Sharia fintech. A quantitative approach was employed using a survey method, with data collected from 120 Generation Z respondents domiciled in Aceh Province, Indonesia. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that Islamic financial literacy and digital payment both have a positive and significant effect on the intention to use Sharia fintech. This indicates that better understanding of Islamic financial principles and familiarity with digital transactions increase users’ readiness to adopt Sharia-based financial technology. The findings highlight the importance of integrating financial literacy and digital experience in promoting Sharia fintech adoption, particularly within the Aceh context. This study provides useful insights for policymakers and fintech providers in developing strategies to enhance the use of Islamic digital financial services.